Effect of a multimodal analgesia strategy on remifentanil daily consumption in mechanically ventilated adult ICU patients: study protocol for a randomised, placebo-controlled, double-blind, parallel-group clinical trial - Thibault Mura; Jean-Yves Lefrant; Remy Widehem; Camille Nicolet; Violaine Delannoy; Laurie Barthelemi; Ian Soulairol; Claire Roger (BMJ Open, 2025)
Introduction Intensive care unit (ICU) patients under mechanical ventilation experience mild-to-severe pain. International guidelines emphasise the importance and benefits of multimodal analgesia to minimise opioid consumption and its side effects. However, no recommendation about drugs or protocol has been formulated. The aim of the Opioid-Free Analgesia in Intensive Care Unit study is to assess the feasibility of a standardised multimodal analgesia strategy and its benefits following the impact of remifentanil sparing in ICU patients.Methods and analysis 50 mechanically ventilated adult patients will be recruited in a randomised, placebo-controlled, double-blind, feasibility trial. In the interventional group, patients will receive a standardised multimodal analgesia, initially receiving nefopam and tramadol, implementing with ketamine if patients remain painful, and then implementing with remifentanil with escalating doses in case of insufficient analgesia. In the control group, patients will receive remifentanil, implementing doses gradually to achieve analgesia. The primary outcome will be the daily consumption of remifentanil between the 24th and 48th hour after inclusion. Secondary outcomes will include drug tolerance, mechanical ventilation duration, ICU and hospital length of stay, 28-day and 90-day mortalities and 90-day opioid consumption.Ethics and dissemination The study protocol was accepted by the Nîmes University Hospital’s research committee, the French ethics committee (Institutional Review Board OUEST IV) and the French National Agency for the Safety of Medicines and Health Products (ANSM).Trial registration number ClinicalTrials.gov: NCT05825560